Dimensions of Advocacy for Exclusive Breastfeeding Policy in Banda Aceh City - Gusweni, Mira; Agustina, Agustina; Wardiati, Wardiati; Naflah, Sajidatun; Taufik, Taufik (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
The achievement of exclusive breastfeeding in Banda Aceh City is still categorized as low from the national target. This problem requires efforts to be made by stakeholders, one of which is through advocacy. This study aims to analyze the dimensions of exclusive breastfeeding policy advocacy in Banda Aceh City. This study used a descriptive qualitative approach with data collection techniques in the form of interviews through open-ended questions. Field observations were conducted in the form of observations of breastfeeding socialization and education activities. Secondary data was collected by reviewing documents relevant to the research. The results found that exclusive breastfeeding policy advocacy activities in Banda Aceh City were not optimal. There is a weakness in the action dimension of advocacy, where stakeholders in the implementation of the breastfeeding program are still running independently.  There is no collective action among stakeholders. The collective action of stakeholders in the implementation of the exclusive breastfeeding program is important to produce optimal breastfeeding outcomes. Optimization of exclusive breastfeeding achievements can be obtained if stakeholders collaborate together in a roadmap of breastfeeding programs and activities in Banda Aceh City.